DRESCRIPTION OF PHARMACEUTICAL SERVICES QUALITY AND OUTPATIENT SATISFACTION IN PHARMACY INSTALLATION OF PKU MUHAMMADIYAH CEPU HOSPITAL - fx sulistiyanto wibowo S; Dian Trisnawati (Dian Nuswantoro Semarang, 2020)
Hospitals as public health services need to provide quality services. Patient satisfaction is a key indicator of health facility standards. The quality of pharmacy services that can be seen from patient satisfaction, with the existence of this study is expected to improve pharmaceutical services at PKU Muhammadiyah Hospital Cepu. This research is to find out the quality of service and the satisfaction of outpatients in PKU Muhammadiyah Cepu Hospital Pharmacy Installation. The study used a descriptive observational research with purposive sampling method in January - March 2020. Data were collected from 110 respondents using a questionnaire. The results of the 110 respondents get the most age categories 46-55 years, 29 respondents (26.36%). The most gender is female, 58 respondents (52.73%). The highest level of education is high school / vocational education with 61 respondents (55.45%) and other types of occupational categories, 28 respondents (25.45%). From the results of calculations and data analysis, on each indicator obtained the following percentages: 79.34% reliability, 77.95% responsiveness, 85.71% empathy, 79.77% tangibility and 80.98% guarantee. It was completed that the quality of service and satisfaction of outpatients in the Pharmacy Installation of PKU Muhammadiyah Cepu Hospital overall was 80.98% with a very satisfied satisfaction classification.Keywords: service quality, satisfaction, outpatient care, Hospital